BEBERAPA KASUS ABSES HATI AMUBA - Junita, Arini; Widita, Haris; Soemohardjo, Soewignjo (journal of internal medicine; Vol. 7, No. 2 Mei 2006)
Amoebiasis is an infection caused by Entamoeba hystolitica intestinal protozoa. Extraintestinal complication is liver abscess (amoebeic liver abscess). The highest prevalence is in tropical and developing country, which have poor sanitation, bad sosioeconomic condition, not well nutrition status, and in area which strain E. Hvstotistica is high. About 10% from all people in the world had this infection, but only 10% became clinically. Amoeboic liver abscess is handled with chemotherapy using nitromidazole derivate, aspiration or drainage with surgery. In case which needed operation, mortality is 12%. And if there is a amoeboic peritonitis, the mortality approximately 40% - 45%, High mortality rate is caused by severe condition. Malnutrition, icteric or shock. Patient died ussually caused by septic condition or hepatorenal syndrome. In this moment, we will report three case of liver abscess with variable size, which made differential decisiton treatment. One case is liver abscess which contain 4.5 L after done surgery drainage.
Keywords: amoebic liver abscess, mortality, treatment